Hepatitis C Virus (HCV) Care Continuum Outcomes and HCV Community Viral Loads Among Patients in an Opioid Treatment Program. (2nd September 2020) - Jordan, Ashly E; Cleland, Charles M; Schackman, Bruce R; Wyka, Katarzyna; Perlman, David C; Nash, Denis
Abstract: Background: Hepatitis C virus (HCV) remains endemic among people who use drugs (PWUD). Measures of HCV community viral load (CVL) and HCV care continuum outcomes may be valuable for ascertaining unmet treatment need and for HCV surveillance and control. Methods: Data from patients in an opioid treatment program during 2013–2016 were used to (1) identify proportions of antibody and viral load (VL) tested, linked-to-care, and treated, in 2013–2014 and 2015–2016, and pre- and postimplementation of qualitative reflex VL testing; (2) calculate engaged-in-care HCV CVL and "documented" and "estimated" unmet treatment need; and (3) examine factors associated with linkage-to-HCV-care. Results: Among 11 267 patients, proportions of HCV antibody tested (52.5% in 2013–2014 vs 73.3% in 2015–2016), linked-to-HCV-care (15.7% vs 51.8%), and treated (12.0% vs 44.7%) all increased significantly. Hispanic ethnicity was associated with less linkage-to-care, and Manhattan residence was associated with improved linkage-to-care. The overall engaged-in-care HCV CVL was 4 351 079 copies/mL (standard deviation = 7 149 888); local HCV CVLs varied by subgroup and geography. Documented and estimated unmet treatment need decreased but remained high. Conclusions: After qualitative reflex VL testing was implemented, care continuum outcomes improved, but gaps remained. High rates of unmet treatment need suggest that control of the HCV epidemic among PWUD will require expansion of HCV treatment coverage.